Update on the Financing of the Fund's Concessional Assistance and Debt Relief to Low-Income Member Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper updates the quota data base through 2008 and discusses implications for members' calculated quota shares. A subsequent staff paper will review key issues related to the realignment of quota shares and present additional illustrative simulations, for discussion by the Committee of the Whole in early July.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet